The mediating effect of stakeholder influence capacity on the relationship between corporate social responsibility and corporate financial performance - Karaye, Yusuf Ibrahim; Ishak, Zuaini; Che Adam, Noriah (Elsevier Ltd., 2014)
Corporate social responsibility (CSR) and corporate financial performance (CFP) has been examined extensively in the literature.Majority of the studies suggested a positive relationship and few others found neutral, negative and/or curvilinear relationships.Hence this development calls for a mediating mechanism on the relationship between CSR and CFP.This paper proposes to provide a framework that explains how and why CSR leads to CFP by promoting a potential mediator namely stakeholder influence capacity (SIC).Based on the literature reviewed, this paper proposes three variables which can be used to implement the framework at firm level. The variables are corporate social responsibility, stakeholder influence capacity and corporate financial performance.